General physics 2 - Santos, Gil Nonato (Sampaloc Manila : Rex Book Store, Inc., 2022)
"This textbook covers the following topics: Electric Charges, Circuitry, Electromagnetism, Mirrors and Lenses, and Introduction to Modern Physics. The worktext focuses on the concepts in physics combined with hands-on experiments through laboratory investigation. All activities, teaching and assessment strategies were designed ad inspired by the Filipino Whole Learner model. This worktext follow the key stage, grade level, content, and performance standards on how to solve problems in physics. Moreover, the classroom learning will lead to a career task and point of integration between the concepts and real-world applications. The laboratory investigation is interactive where the students are engaged in hands-on experiments with locally available materials. Teachers also benefit from adopting this worktext since it is accompanied by a teacher's resource material (TRM) with answer key as well as other teaching aids."
Includes references and index.
English text.
Keywords: Physics